Implementasi Media Manekin Dalam Pembelajaran Fiqih Materi Pengurusan Jenazah Kelas IX di MTs Muhammadiyah 2 Purbalingga - Ayu Setyasih1, Putri; Mayasari, Novi (Jurnal Pendidikan Agama Islam, 2025)
In fiqh learning, the material on funeral mangemnt is one of the materials that teaches skills in implementing religious teaching practices. Thus, efforts are needed to improve students’ understanding and skills carried out by educators. One effort that can be realized is throught the use of learning media. One the media used at MTs Muhammadiyah 2 Purbalingga is mannequin media. The purposes of this study was to describe and analyze the implementation of mannequin media in fiqh learning on funeral management for class IX at MTs Muhammadiyah 2 Purbalingga. This study used a field research method with a qualitative descriptive approach. The location studied was MTs Muhammadiyah 2 Purbalingga. The research subject included curriculum vice principal, fiqih teachers, and class IX students. The result of the study on the implementation of mannequin media in fiqh learning on funeral management for class IX at MTs Muhammadiyah 2 Purbalingga, namely carried out with the steps of planning, implementation, and evaluation. The planning stage is by making RPP and preparing mannequin media and equipment to be used. The second step is the implementation of media in learning by presenting mannequin media and explaining the learning objectives presented with media. The last stage is evaluation and follow-up by evaluating student learning outcomes and also evaluating media presentation. In the stage, it is necessary to realize that each media has a number of advantages and disadvantages. One of the advantages is that mannequin media is easily accepted and understood by students, but besides that this media also has disadvantages, namely that it requires routine maintenance so that it is not easily damaged.